Plato, Gorgias, and Trickster: Seeking Rhetoric's Muse - Keith Rhodes (Journal of the Assembly for Expanded Perspectives on Learning, 1998)
From an historical perspective, rhetoric is the premier Tricksterish art. Seeing this permits us to re-evaluate Plato's role in the history of rhetoric and re-think current practices.